1992
DOI: 10.1093/ije/21.5.893
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipids and their Correlates in Chinese Urban and Rural Populations of Beijing and Guangzhou

Abstract: In 1983 and 1984, surveys were conducted in four Chinese population samples, urban and rural for both Beijing and Guangzhou, as part of PRC-USA collaborative research in cardiovascular and cardiopulmonary epidemiology. Serum total cholesterol (TC), HDL-cholesterol (HDL-C), and triglycerides (TG) were measured in 4280 men and 4695 women aged 35-54 years, in laboratories standardized by the US Centers for Disease Control. Age-adjusted mean serum TC was higher in urban than rural samples and generally higher in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 0 publications
6
17
1
Order By: Relevance
“…Overall, 35.4% of participants had dyslipidemia (including high TC, high LDL-C, low HDL-C, high TG, or self-reported current use of anti-dyslipidemia medications). Our findings, together with other studies 5,18,19) , confirmed that the prevalence of dyslipidemia is increasing in China. For example, in a cross-sectional study among 6412 rural hypertensives aged ≄ 35years, 37.2% had dyslipidemia 5) .…”
Section: Discussionsupporting
confidence: 90%
“…Overall, 35.4% of participants had dyslipidemia (including high TC, high LDL-C, low HDL-C, high TG, or self-reported current use of anti-dyslipidemia medications). Our findings, together with other studies 5,18,19) , confirmed that the prevalence of dyslipidemia is increasing in China. For example, in a cross-sectional study among 6412 rural hypertensives aged ≄ 35years, 37.2% had dyslipidemia 5) .…”
Section: Discussionsupporting
confidence: 90%
“…China populations than in a Belgian population. 37 In the People's Republic of China (PRC) -U S A Cardiovascular and Cardiopulmonary Epidemiology Study, Tao et al 38 report serum lipids from Chinese aged 35 to 54 years in urban and rural populations in Beijing and Guangzhou. After correction by a factor of 1.03 for the serum-plasma difference, Taipei men had higher total cholesterol, LDL-C, and trigryceride levels than urban Beijing men; however, they had similar HDL-C values.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due in part to the beneficial effects of a Chinese diet, which results in a low mean plasma cholesterol concentration and a low incidence of CHD in the general population. 7 - 8 However, in Japan heterozygous FH is a relatively common clinical disorder that is associated with a high incidence of premature CHD despite the same apparent protective effect of the traditional Japanese diet on the general population. 910 In this study we have examined whether the nature of the mutation or mutations in the LDL-receptor gene that cause FH in China can provide an explanation for their apparently minimal impact on plasma cholesterol levels and coronary disease in heterozygous individuals.…”
Section: F Amilial Hypercholesterolemia (Fh) Is An Inher-mentioning
confidence: 99%